2008
DOI: 10.1523/jneurosci.2250-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neurons in a Forebrain Nucleus Required for Vocal Plasticity Rapidly Switch between Precise Firing and Variable Bursting Depending on Social Context

Abstract: Song is a learned vocal behavior influenced by social interactions. Prior work has suggested that the anterior forebrain pathway (AFP), a specialized pallial-basal ganglia circuit critical for vocal plasticity, mediates the influence of social signals on song. Here, we investigate the signals the AFP sends to song motor areas and their dependence on social context by characterizing singing-related activity of single neurons in the AFP output nucleus LMAN (lateral magnocellular nucleus of the anterior nidopalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
199
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(218 citation statements)
references
References 76 publications
17
199
2
Order By: Relevance
“…Previous work has shown that acute inactivation of Area X in anesthetized adult zebra finches tonically disinhibits thalamic neurons, inducing higher spontaneous firing rates in LMAN (34), consistent with findings in mammals (8,35). According to firing-rate models of basal ganglia function, lesions of Area X should increase spontaneous firing rates in LMAN, which, in turn, could mask the normal singing-related rate increases observed in intact birds (36)(37)(38). Alternatively, lesions of Area X could change the firing statistics of LMAN neurons, as predicted by firing-pattern models, with or without affecting their overall firing rates.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Previous work has shown that acute inactivation of Area X in anesthetized adult zebra finches tonically disinhibits thalamic neurons, inducing higher spontaneous firing rates in LMAN (34), consistent with findings in mammals (8,35). According to firing-rate models of basal ganglia function, lesions of Area X should increase spontaneous firing rates in LMAN, which, in turn, could mask the normal singing-related rate increases observed in intact birds (36)(37)(38). Alternatively, lesions of Area X could change the firing statistics of LMAN neurons, as predicted by firing-pattern models, with or without affecting their overall firing rates.…”
Section: Resultssupporting
confidence: 81%
“…In both intact and deaf birds, LMAN neurons increase their discharge before and during singing, consistent with premotor signaling (36)(37)(38). In the absence of Area X, we found that LMAN neurons continued to exhibit robust increases in firing rate before song initiation and during singing (Fig.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…A transition to neuronal burst firing has emerged as a unique mode of sensorimotor information transfer in the forebrain of songbirds and other vertebrates (20,(22)(23)(24)(25)(26). Burst firing has been associated with increased attention/wakefulness (23,27,28), synaptic efficacy (29,30), and discrimination among sensory stimuli (20,24,28) and is thought to depend on the activity of projections from the basal forebrain (e.g., cholinergic projections; ref.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate this elevation in burst firing, a custom software script for burst identification and analysis (CED) was used to process spike trains for bursts consisting of three or more action potentials separated by ≤10 ms (for similar burst parameters, see ref. 25). Burst parameters were quantified in response to each playback stimulus (30 iterations) for both estradiol and FAD experiments as described for spike rate data above.…”
Section: Methodsmentioning
confidence: 99%